Modifications of the rupture envelope in clayey soils with different volumetric stabilizer - Sánchez, A.; Alonso Guzmán, Elia Mercedes; Martínez, Wilfrido; Chávez, H.; Navarrete, M.; Arreola, M.; Borrego, J.; Equihua, L.; Núñez, E.; Miranda, O. (Revista ALCONPAT, 2022)
The modifications of seven different stabilizers (lime, cement, nopal fibers, river sand, volcanic sand, sodium sulphate and gypsum) on a clayey soil of Santiago Undameo, in Michoacan, Mexico, were analyzed to observe the changes in the properties and the rupture envelope. Sieve analysis, hydraulic sedimentation, index properties, compressive strength and Proctor were performed to the natural soil; while the variation of the index properties and the rupture envelope were determined for the stabilized mixtures. The additions improved the behavior of the high plasticity soil, diminishing the volumetric deformations and increasing the mechanical resistance, shear strength and angle of internal friction. This research contributes positively to the restoration of earthen heritage buildings, civil works, construction pathologies and construction technologies. The research was performed in the laboratory under international standards.